2021
DOI: 10.3389/fcvm.2021.725902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open Repair vs. the One-Stage Hybrid Extra-Anatomic Technique for Distal Aortic Arch Disease Treatment: Mid-term Outcomes With a Risk-Adjusted Analysis

Abstract: Objective: This study aims to compare the short- and mid-term outcomes of the stented elephant trunk (SET) procedure combined with supra-arch branch reconstruction and one-stage hybrid arch repair combined thoracic endovascular aortic repair (TEVAR) with extra-anatomic bypass in the management of distal arch disease.Methods: From January 2009 to January 2019, 97 patients underwent one-stage hybrid arch repair combined with TEVAR with extra-anatomic bypass (HAR group), and 206 patients underwent the SET procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A Chinese report comparing the surgical and hybrid procedures' outcomes reported similar drop in survival after five years in hybrid group (from 82% at five years to 43.6% at nine years) compared to the surgical supra-arch repair which was dedicated to the endoleaks in the hybrid group. [9] Another Chinese study reported 78.3% survival rate at seven years. [10] One of the main advantages expected from the antegrade perfusion and avoiding or limiting the TCA durations is to decrease the postoperative stroke rate.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese report comparing the surgical and hybrid procedures' outcomes reported similar drop in survival after five years in hybrid group (from 82% at five years to 43.6% at nine years) compared to the surgical supra-arch repair which was dedicated to the endoleaks in the hybrid group. [9] Another Chinese study reported 78.3% survival rate at seven years. [10] One of the main advantages expected from the antegrade perfusion and avoiding or limiting the TCA durations is to decrease the postoperative stroke rate.…”
Section: Discussionmentioning
confidence: 99%
“…The frozen elephant trunk (FET) technique is an effective surgical repair for acute and chronic aortic dissections (1)(2)(3)(4). The covering of proximal tears in the descending aorta through an FET stent-graft induces false lumen thrombosis and promotes satisfactory aortic remodeling (5).…”
Section: Introductionmentioning
confidence: 99%